A Review of International Legal Instruments : Facilitation of Transport and Trade in Africa, Second Edition - de Matons, Jean Grosdidier (World Bank, Washington, DC, 2014)
This is the second edition of the 2003 paper entitled "Facilitation of transport and trade in Sub-Saharan Africa : a review of international legal instruments - Treaties, conventions, protocols, decisions, directives." Three major reasons motivated this update and an expansion of its scope. First, African countries are increasingly cooperating, especially in the area of corridors, to achieve full connectivity, mobility and accessibility. To that end, they are concluding new agreements and conventions. Second, this new edition has been extended to the whole of the African continent, including the Maghreb, which was not in the previous inventory. Third, air transport and associated agreements and conventions were added at the request of countries. Indeed, the future of air transport in Africa is bright. It is likely that it becomes an affordable mode of transport to reach remote areas.